Pemikiran Ekonomi Islam Kontemporer : Muhammad Baqir Al- Sadr, Ibrahim Umar Vadillo, Dan M. Umer Chapra - Nazwa Alya Alkhansa; Nuni Asnita Barasa; Ahmad Dwi Pramanda; Rangga Heriyadi; Fadlan Arrasyid Bintang (Journal of Islamic Economics and Finance, 2024)
Money is an important component of existence. We call the system created by the exchange of certain contracts a financial transaction. These exchanges are simply an attempt to meet basic needs. Muhammad Baqir Ash Sadr consistently discusses the state of Islamic economics in his writings, consistently stating his rejection of colonial economics (conventional economics). The traditional economic perspective on economics and the true understanding of economics are not the same. This view is based on the scientific theory of economics which argues that scarcity of resources in the economy causes economic problems. According to M. Umer Chpra, everyone who pursues entrepreneurship is naturally influenced by their worldview and assumptions about the nature of the universe and human existence.